Comparing the Effects of Traditional and Continuous Training of Practical Microbiology Course on Students Learning - Zahra Rashki-Ghalehnoo; Dariush Saadati; Omid Tadjrobehkar (Kerman University of Medical Sciences, 2015)
Background & Objective: There are different views toward the efficacy of different methods of practical training Each method has advantages and disadvantages in terms of its effect on learning cost speed and simplicity This study was performed with the aim to compare the effect of practical microbiology course through traditional and continuous methods of training on practical skills learning academic achievements and satisfaction among pharmacy students of Zabol University of Medical Sciences Iran Methods: This experimental study was performed on 79 2nd semester pharmacy students The participants were randomly allocated to two groups with equal mean IQ score using Raven IQ test The traditional and continuous methods of training were randomly applied to the two groups Mean final exam scores of the two groups based on station exam final reports and written tests were calculated and compared using Students ttest We also assessed the satisfaction of students with regard to the training methods using a relevant questionnaire Results: Mean scores of the station (468) and written (843) exams obtained using continuous method were significantly higher than that using the traditional method (417 and 751 respectively) Moreover students were more satisfied with the continuous method than the traditional method Conclusion: The continuous method of training had greater impact on learning of practical skills than the traditional method Thus the application of this method in other medical universities in order to provide a suitable setting for further learning is recommended